Pelatihan Digital Content Creation bagi Creativepreneur di Desa Limbung Kabupaten Kubu Raya - Siallagan, Debbie Yuari; Prestoroika, Era; Lubis, Laila Nurfitrah; Yudimamase, Adiyath Randi; Hidayati, Asri; Depriyani, Magdalena; Trimawarni, Andjani; Meisari, Winda Chelsea; Sari, Eka Mustika (CV Global Research Publication, 2025)
Limbung Village in Kubu Raya Regency had numerous business opportunities. The village also has innovative and creative human resources, particularly through the youth community group in the village. Additionally, the community’s desire to develop businesses based on local resources and to utilize the village’s potential to build and grow new businesses was evident. The daily routines of the community were inseparable from the internet, particularly in the use of social media. This encouraged the community, especially the younger generation in Limbung Village, to actively create digital content. The Kristal Youth Organization of Limbung Village had two types of businesses that had been running for quite some time: the sale of office stationery and printing, as well as catfish farming, which was managed creatively. The creativity involved included producing catfish feed using a self-made production machine. Creativepreneurs, the business owners who ran their enterprises creatively by continuously innovating to ensure their businesses thrived, were active in the village. However, the utilization of these efforts had not yet significantly increased the income of the younger generation, indicating that the use of social media was not yet optimal. The lack of understanding among creativepreneurs in leveraging social media was a core issue that needed to be addressed. Strong skills in managing social media could provide significant benefits for entrepreneurs, such as reaching a broader market and increasing the potential for greater profits. As a result of these activities, creativepreneurs had become capable of creating engaging digital content using editing applications and had also contributed to promoting the village’s businesses and products.